HOW TO DETERMINE THE TEACHERS THE PSYCHOLOGICAL PORTRAIT OF STUDENT? - Nevedomska, Yevgeniya A.; Мihajlovska, Anna P. (Educological discourse, 2015)
The article deals with the concept of asymmetry of the human brain, set goals and objectives of the pilot study discloses a technique for carrying out the experiment. The study showed that functional asymmetry of the brain affects the temperament and memory processes of the student. The study revealed certain regularities between brain asymmetry coefficient students and their peculiarities of temperament and memory processes. These data will be useful to teachers in the educational process.